Differences of Vital Lung Capacity and FEV1/FVC Ratio on Children in Urban and Rural - Raden Ayu Tanzila; Milla Fadliya Bustan (Global Medical & Health Communication (GMHC), 2018)
Urban areas are places with high levels of air pollutant. This air pollution causes decreased lung function and obstruction in the respiratory tract. The absorption of dust particles and pollution is inhaled into the lungs through the respiratory mechanism. The entry of toxic material will react with the cells causing free radicals that will damage cells, especially in the respiratory system. This study was aimed to knowing the differences vital lung capacity and forced expiration volume in 1 second/forced vital capacity (FEV1/FVC) ratio in children in urban areas with high level pollution and in rural areas not exposed to pollution. This study was an observational analytic study, implemented in September–December 2016 with a total sample of 70 children consisting of 35 children in Palembang city and 35 children in Musi Rawas area. Data analysis to determine the differences of lung vital capacity and FEV1/FVC ratio in children in rural and urban with independent t test. The result showed that the average value of urban vital lung capacity in urban (1,205 mL) was lower than the mean value of vital lung capacity of children in rural (1,493 mL) and there was significant difference in the value of vital lung capacity in rural children and urban (p=0.004). The ratio of FEV1/FVC for children in urban areas (91.05%) was lower than the ratio of FEV1/FVC for children in rural (93.96%) as well as a significant difference in the ratio of FEV1/FVC in rural and urban children (p=0.001). In conclusion, the mean value of lung vital capacity and the ratio of FEV1/FVC of children in urban areas is lower than mean value of vital lung capacity of children in rural areas. PERBEDAAN KAPASITAS VITAL PARU DAN RASIO FEV1/FVC PADA ANAK DI PERKOTAAN DAN PEDESAANPerkotaan merupakan tempat dengan tingkat paparan polusi udara yang tinggi. Polusi udara ini menyebabkan penurunan fungsi paru-paru dan obstruksi pada saluran pernapasan. Absorpsi partikel debu dan polusi terhirup masuk paru-paru melalui mekanisme pernapasan. Masuknya bahan toksik ini akan bereaksi dengan sel sehingga menimbulkan radikal bebas yang akan merusak sel terutama pada sistem pernapasan. Tujuan penelitian ini adalah mengetahui perbedaan kapasitas vital paru dan rasio forced expiration volume in 1 second/forced vital capacity (FEV1/FVC) pada anak di perkotaan dengan tingkat polusi yang cukup tinggi dibanding dengan pedesaan yang tidak terpapar polusi. Penelitian merupakan penelitian observasional analitik dilaksanakan pada bulan September–Desember 2016 dengan jumlah sampel 60 orang terdiri atas 30 orang anak di Kota Palembang dan 30 anak di daerah Musi Rawas. Analisis data untuk mengetahui perbedaan kapasitas vital paru dan rasio FEV1/FVC pada anak di pedesaan dan perkotaan menggunakan uji t tidak berpasangan. Hasil penelitian didapatkan nilai rerata kapasitas vital paru anak di perkotaan (1.205 mL) lebih rendah daripada nilai rerata kapasitas vital paru anak di pedesaan (1.493 mL) dan didapatkan perbedaan bermakna nilai kapasitas vital paru antara anak di perkotaan dan pedesaan (p=0,004). Nilai rasio FEV1/FVC anak di perkotaan (91,05%) lebih rendah daripada rasio FEV1/FVC anak di pedesaan (93,96%) yang berbeda bermakna (p=0,001). Simpulan, nilai rerata kapasitas vital paru dan rasio FEV1/FVC anak di daerah perkotaan lebih rendah daripada nilai rerata kapasitas vital paru anak di daerah pedesaan.